THE SUPREME COURT ON PUBLIC-UTILITY DEPRECIATION. - Mason, Perry (The Accounting Review, 1936)
Abstract The article focuses on opinions expressed by the justices of the Supreme Court of the United States on depreciation that had a marked influence upon the subsequent decisions of the state and the Federal public utility commissions. In no case prior to the Knoxville Water Company case in 1909 has there been more than an incidental reference to depreciation, or a brief discussion which indicates an entirely inadequate knowledge of its nature and problems. Definite recognition was given of the necessity of a utility keeping its property in good service condition, but little or no appreciation was evidenced of the function of depreciation accounting methods. A statement was made in the case of United States v. Kansas Pacific Railway that only such expenditures are actually made, can with any propriety be claimed as a deduction from earnings, and the creation of an unspent reserve through periodic charges to operations was prohibited.